The Wage Labor Market and Inequality in Vietnam in the 1990s - Gallup, John Luke (World Bank, Washington, DC, 2014)
Has the expansion of wage employment in Vietnam exacerbated social inequalities, despite its contribution to income growth? Gallup uses the two rounds of the Vietnamese Living Standards Survey (VLSS) to evaluate the contribution of wage employment to inequality and income growth over the period of rapid economic growth in the 1990s following market reforms. If Vietnam sustains its economic development in the future, wage employment will become an ever more important source of household income as family farms and self-employed household enterprises become less prevalent. Observing the recent evolution of wage employment compared with farm and non-farm self-employment provides clues as to how economic development will change Vietnamese society, in particular its impact on income inequality within and between communities. The author shows that standard methods for calculating income inequality can be severely biased due to measurement error when decomposing the contribution of different sectors, regions, or groups to overall inequality. A new method for consistent decomposition of inequality by income source shows that despite the rapid growth of wages in the 1990s, wage inequality fell modestly. Contrary to the results of uncorrected methods, wage employment contributes a roughly similar amount to overall income inequality as other nonagricultural employment (household enterprise and remittances, mainly). Agricultural income actually reduces overall income inequality because inequality between agricultural households is much lower than inequality between nonagricultural households, and agricultural income has a lower correlation with other income sources. Wage employment has not been the locus of growing disparity between the haves and the have-nots in Vietnam. A declining share of agriculture as the economy grows in Vietnam means that income inequality will rise, assuming that within-sector inequality does not change. This rising inequality, due to the shrinking share of agriculture, will be difficult to avoid without giving up economic growth and rapid poverty reduction in Vietnam. Historically, the process of economic development has always brought about a transition out of small farms and household enterprises into wage employment as worker productivity increases and non-household enterprises dominate the economy.